Feline politics in organization: The nine lives of Olly the cat. (May 2016) - O'Doherty, Damian P.
The appearance of 'Olly the cat' on the doorsteps of a major UK international airport provides occasion to reconsider the role of the animal in organization and offers suggestive insight into how we might have to learn new ways of being within extended multi-species or interspecies ontologies. Olly is found to lead multiple lives that cannot be reduced to the status of object or media of human intentionality. Her increasing political involvement in the management and organization of the airport challenges orthodox understanding of agency and organizational action. As the ethnography becomes progressively more implicated in the entanglements between human and animal, the concept of 'feline politics' is proposed and deployed. This allows research to retain focus on actions and behaviour and modes of thinking that would ordinarily be occluded by conventional modes of organizational representation. In these ways the ethnography moves beyond the interpretative and symbolic treatment of organization analysis and finds resource in the recent 'ontological turn' in the social sciences. Embracing what is the inevitable participation of the social sciences in the reflexive and recursive enactment of its phenomena, the ethnography discovers new potentialities and new capacities for action as emergent properties of 'the human' and 'the animal' were mutually learnt, exchanged and acquired. This article adds to what we know about the limits of management as it confronts a radical undecidability characterized by the co-existence of multiple and interacting ontological becomings.